1996
DOI: 10.1177/030006059602400104
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Roxithromycin on the Generation of Reactive Oxygen SpeciesIn Vitro

Abstract: The effect of roxithromycin (ROM), a new oral semi-synthetic macrolide, on the generation of reactive oxygen species (ROS), using human neutrophils and a cell-free, xanthine-xanthine oxidase system was examined. The species investigated were the superoxide radical anion (O2-), hydrogen peroxide (H2O2), and the hydroxyl radical (OH.). ROM effectively inhibited the generation of O2-, H2O2 and OH. by human neutrophils. On the other hand, the drug did not markedly affect the ROS levels generated in the xanthine-xa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Akamatsu et al showed that RXM decreases production of ROIs of neutrophils [11]. Using xanthine-xanthine oxidase system, they also reported that RXM did not affect the level of ROIs in a cell-free system [11]. These results coupled with ours indicate that the effect of RXM is due to the inhibition of ROIs production, which depends on viable cell metabolism.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Akamatsu et al showed that RXM decreases production of ROIs of neutrophils [11]. Using xanthine-xanthine oxidase system, they also reported that RXM did not affect the level of ROIs in a cell-free system [11]. These results coupled with ours indicate that the effect of RXM is due to the inhibition of ROIs production, which depends on viable cell metabolism.…”
Section: Discussionsupporting
confidence: 74%
“…decreased production of ROIs in SVHK cells. Akamatsu et al showed that RXM decreases production of ROIs of neutrophils [11]. Using xanthine-xanthine oxidase system, they also reported that RXM did not affect the level of ROIs in a cell-free system [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that roxithromycin is transferred at therapeutic concentrations into acne lesions upon oral administration (data not shown), has antibacterial activity against P. acnes [5,6] and significantly inhibits in a concentration-dependent manner the 3 types of neutrophil-derived active oxygen species superoxide radical anion, hydrogen peroxide and hydroxyl radical [15]. These suggest that there is a possibility that roxithromycin is effective in the treatment of acne because it is transferred sufficiently into acne lesions in vivo, reduces bacterial load, inhibits the production of bacterial lipase and neutrophil chemotactic factor, which are extracellular inflammation-inducing agents produced by P. acnes, and inhibits the excessive production of active oxygen species caused by neutrophil migration into acne lesions.…”
Section: Discussionmentioning
confidence: 96%
“…For example, erythromycin was shown to increase apoptosis and decrease IL-8 secretion by human neutrophils [11] . Erythromycin derivatives, including roxithromycin and axithromycin, have been shown to inhibit the production of superoxide from neutrophils [12][13][14][15] . 207 Little is known regarding the effects of clarithromycin on infl ammatory cells.…”
Section: Introductionmentioning
confidence: 99%